Validity of the Nepali Ask Suicide Screening Questions tool for medical inpatients - Daman R Poudel; Arun K Sharma; Ram H Chapagain; Manisha Chapagai; Nathan J. Lowry; Mahesh R Sigdel; Krishna P Bista; Rahul Pathak; Arun Kunwar; Janna Patterson; Terrell Carter; Lisa M. Horowitz (BMC Psychiatry)
Abstract Background Nepal has one of the highest youth suicide rates in the world. Suicide screening is rarely performed during hospitalization, partly due to the lack of validated tools in the local language. We evaluated the validity of the Nepali version of the Ask Suicide-Screening Questions (ASQ) tool in youth population in medical inpatient settings. Methods We conducted a cross-sectional validation study at two urban hospitals in Nepal between January and July 2022. Patients aged 10 to 24 years admitted to medical wards were recruited through convenience sampling. Patients with significant cognitive impairment, non-fluent in Nepali, or planned early discharge limiting participation were excluded. Trained nurses administered the ASQ followed by the adolescent version of Patient Health Questionnaire (PHQ − 9) and completed a demographic survey. Thereafter a separate team of psychologists, blind to ASQ results, conducted a brief suicide safety assessment (BSSA) as the gold standard for suicide risk screening. Results All study procedures were completed by 309 [54.0% male, mean age = 15.79(± 4.2) years] participants and were included in analysis. In our sample, 15.9% (49/309) screened positive with ASQ; 8.4% (26/309) had elevated suicide risk on the BSSA. The ASQ demonstrated good sensitivity (77%; 95% CI: 56–91), specificity (90%; 95% CI: 86–93), positive predictive value (41%; 95% CI: 27–56) and negative predictive value (98%; 95% CI: 95–99) against BSSA. Conclusion The Nepali version of ASQ is a good, brief screening tool for identifying suicidal risk. Further validation in wider populations including outpatient setting and routine implementation in clinical practice should be considered.